High sensitive C-reactive protein and interleukin 6 in atrial fibrillation with rheumatic mitral stenosis from Indian cohort - Sharma, Gautam (Indian Heart J, 2017)
INTRODUCTION: Presence of chronic low grade inflammation has often been implicated in the etiology of atrial fibrillation (AF). Whether pre-existing inflammatory state promotes AF or initiation of AF activates inflammation is a dilemma among clinicians. This study investigates the role of high sensitive C reactive protein (hs-CRP) and interleukin 6 (IL-6) in AF with rheumatic mitral stenosis (Rh-MS) as markers of chronic inflammation. METHODS: This case control cohort included sixty five (n = 65) Rh-MS patients having other valve lesions as trivial to mild. Out of them twenty nine (n = 29; group C) had baseline AF and rest were normal sinus rhythm (NSR). A 24 h holter recording was done in NSR patients to diagnose paroxysmal AF/tachyarrhythmia forming group B (n = 12) and not having any tachyarrhythmia were designated as NSR; group A (n = 24). RESULTS: hs-CRP and IL6 showed statistically significant increase in group C (permanent AF) compared to group A (95% CI: 4.2–0.9, p = 0.007; 95% CI: 1.2–0.89; p = 0.05 respectively), while it was non significant between group A and group B (p > 0.05). A weak positive correlation was observed with hs-CRP and left atrial volume index (LAVi) (r = 0.45, p = 0.06) in AF group as compared to NSR group. 68.2% of patients in AF group (27/41) had moderate to severe spontaneous echo contrast (SEC) as compared to 37.5% (10/24) in NSR group. CONCLUSION: Increased hs-CRP and IL-6 levels in the paroxysmal and permanent AF group may favour the hypothesis that low grade chronic inflammation could be the cause of atrial fibrillation than a consequence.